2018
DOI: 10.1159/000492680
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-Leukocyte Cross-Talk: Impact on Immune Polarization and Immunometabolism

Abstract: Biofilms are bacterial communities contained within an extracellular matrix, which can colonize both native tissues and artificial surfaces. In particular, indwelling medical devices and prosthetic implants are targets for biofilm formation because they facilitate bacterial attachment via host proteins that coat the foreign body. Biofilm infections are particularly challenging to treat, since they are not readily cleared by antibiotics, require invasive procedures to eradicate, and are prone to recurrence. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 52 publications
2
81
0
Order By: Relevance
“…We quantified this response for the first time and showed that it is significantly increased with the planktonic form after 4 h, compared to that in control mice. The absence of significant differences between the control and biofilm conditions could have been due to early phagocyte killing, as previously reported [4,5,17]. After 24 h, the inflammatory response was considerable and comparable for the two bacterial forms.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We quantified this response for the first time and showed that it is significantly increased with the planktonic form after 4 h, compared to that in control mice. The absence of significant differences between the control and biofilm conditions could have been due to early phagocyte killing, as previously reported [4,5,17]. After 24 h, the inflammatory response was considerable and comparable for the two bacterial forms.…”
Section: Discussionsupporting
confidence: 71%
“…The immune responses elicited by biofilms have been described as specific and ineffective thus promoting bacterial persistence and the establishment of chronic infections [4]. Different immune evasion mechanisms have been proposed to be involved, including phagocyte direct killing (macrophages, neutrophils), specific recruitment of myeloid-derived suppressor cells (MDSCs) and macrophage polarization towards an anti-inflammatory phenotype [4,5]. These results were mostly obtained during experiments performed in vitro in which biofilms were exposed to monocytes or neutrophils, or both [6].…”
Section: Introductionmentioning
confidence: 99%
“…TLR2, but not TLR9, is critical for bacterial containment during S. aureus craniotomy infection Infectious complications after craniotomy are typically not able to be resolved without performing surgery to debride the infected bone flap and surrounding purulent material [28]. This is because bacteria adherent to the bone flap have formed a biofilm, which is recalcitrant to antibiotics and immune-mediated clearance [4,29]. Once the biofilm has been disrupted, by aggressive disinfection of the bone flap intra-operatively or removal if the bone flap cannot be salvaged, the remaining bacteria are antibiotic susceptible, since they become metabolically active.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilms are major drivers of bacterial pathogenesis in the context of chronic infections. Historically, protection against immune attack alongside antibiotic tolerance, were postulated as the key advantages conferred by these biofilms during infection but research into their role in modulating immunity is gathering momentum (5, 25). In the context of infection, MR and DC-SIGN are considered promoters of regulatory immune mechanisms designed to curtail damaging inflammatory processes and MR and/or DC-SIGN binding are viewed as immune evasion mechanism(s) (11, 12, 26, 27).…”
Section: Discussionmentioning
confidence: 99%